Non-Alcoholic Steatohepatitis: Clinical and Translational Research - Manuela G Neuman; Mihai Voiculescu; Radu M Nanau; Yaakov Maor; Ehud Melzer; Lawrence B Cohen; Mihai Opris; Stephen Malnick (Journal of Pharmacy & Pharmaceutical Sciences, 2016)
The present review includes translational and clinical research that characterize non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH). Clinical and experimental evidence led to the recognition of the key toxic role played by lipotoxicity in the pathogenesis of NAFLD. The current understanding of lipotoxicity suggests that organ injury is initiated by the generation of oxidative metabolites and the translocation of gut-derived endotoxin. These processes lead to cellular injury and stimulation of the inflammatory responses mediated through a variety of molecules. The injury progresses through impairment of tissue regeneration and extracellular matrix turnover, leading to fibrogenesis and cirrhosis. Several cell types are involved in this process, predominantly stellate cells, macrophages and parenchymal cells. In response to inflammation, cytokines activate many signaling cascades that regulate fibrogenesis. This examination brings together research focusing on the underlying mechanisms of injury. It highlights the various processes and molecules that are likely involved in inflammation, immune modulation, and fibrogenesis in the liver. We searched electronic databases (Medline, Embase) for this review. This integrative work investigates different aspects of liver damage and possible repair. We aim to (1) determine the immuno-pathology of liver damage due to steatosis, (2) suggest diagnostic markers of NASH, (3) examine the role of behaviour in the development of NASH, and (4) develop common tools to study steatosis-induced effects in clinical studies. Special accent is put on co-morbidities with renal and neuropsychological disorders. Moreover, we review the evidence in literature on the role of moderate alcohol consumption in individuals that present NAFLD/NASH.